2022
DOI: 10.17305/bjbms.2022.7850
|View full text |Cite
|
Sign up to set email alerts
|

VHL tumor suppressor as a novel potential candidate biomarker in papillary thyroid carcinoma

Abstract: Papillary thyroid carcinoma (PTC) is the most common type of endocrine cancer, with an increasing incidence worldwide. The treatment of PTC is currently the subject of clinical controversy, making it critically important to identify molecular markers that would help improve the risk stratification of PTC patients and optimize the therapeutic approach. The VHL tumor suppressor gene has been implicated in tumorigenesis of various types of carcinoma and linked with their aggressive biological behavior. The role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…The investigation revealed that a group of miR-25-3p, miR-296-5p, and miR-92a-3p were overexpressed in PTC patient samples compared to controls. Moreover, miR-25-3p, miR-296-5p, and miR-92a-3p target the genes AKT1, PLK1, and VHL1, respectively (Table 1) (29,41,46). Furthermore, the diagnostic value was assessed by the areas under the curves (AUC), and the values were statistically significant, with values of 0.727, 0.771, and 0.862, respectively.…”
Section: Analysis Of Micrornas In Blood (Serum/plasma) Of Ptcmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation revealed that a group of miR-25-3p, miR-296-5p, and miR-92a-3p were overexpressed in PTC patient samples compared to controls. Moreover, miR-25-3p, miR-296-5p, and miR-92a-3p target the genes AKT1, PLK1, and VHL1, respectively (Table 1) (29,41,46). Furthermore, the diagnostic value was assessed by the areas under the curves (AUC), and the values were statistically significant, with values of 0.727, 0.771, and 0.862, respectively.…”
Section: Analysis Of Micrornas In Blood (Serum/plasma) Of Ptcmentioning
confidence: 99%
“…The VHL is a tumor suppressor gene that is downregulated in some types of cancer. This gene dysregulation is involved in the development of carcinomas and clinically manifests aggressive behavior ( 29 ).…”
Section: Analysis Of Micrornas In Blood (Serum/plasma) Of Ptcmentioning
confidence: 99%